Calculating the GHG impacts of FLW – toolkits and calculators - Robertson, Kai (2018)
Meeting on food loss and waste as a climate change mitigation strategy November 14, 2018 Hosted by CCAFS Low Emissions Development as part of its Learning Platform on Low Emission Options